Tingkat Pengetahuan Hidrasi, Asupan Cairan, Aktivitas Fisik, dan Status Hidrasi Remaja Usia 12-15 Tahun di Surabaya - Sholihah, Lini Anisfatus; Utami, Ghina Afifa (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2022)
Dehydration is a condition when the body is lacking fluid. Dehydration can impair cognitive performance, memory skills, body endurance, and muscle strength. This research aimed to describe the prevalence of dehydration, the level of knowledge, fluid intake, and physical activity among adolescents in Surabaya. We involved 66 students aged 12-15 years old from grade VII and VIII Junior High School Muhammadiyah 4 Gadung Surabaya. Subjects were interviewed to assess their knowledge level, physical activity level (PAL), and mean water intake. Dehydration status was measured by comparing subjects’ urine color to a chart developed by Armstrong. An independent t-test was performed to see the difference in mean water intake between subjects according to their knowledge level and gender. We found that 79% of the subjects still have low knowledge regarding the importance of hydration, 97% of subjects are physically inactive, 67% consume water less than their needs, and 67% of them are dehydrated. We did not find any significant difference in knowledge level, water intake, and PAL among dehydrated and non-dehydrated groups. Most of the subjects are dehydrated and have a lower knowledge level regarding hydration. It is necessary to educate adolescents through school channels to improve their knowledge and water intake.